1987
DOI: 10.1111/j.1365-3113.1987.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomy of the Pollenia rudis species‐group in the Holarctic Region (Diptera: Calliphoridae)

Abstract: Abstract. A rudis species‐group is defined within Pollenia Robineau‐Desvoidy, and new characters found useful in the taxonomy of this genus are presented. P.rudis (Fabricius), P.angustigena Wainwright, stat.rev. and P.pseudorudis Rognes are redescribed. P.hungarica sp.n., P.longitheca sp.n. and P.luteovillosa sp.n. are described as new to science. A key is provided, and the terminalia of both sexes are illustrated for all the species. Some features of the puparia are figured for the species where these are kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 12 publications
(14 reference statements)
1
57
0
Order By: Relevance
“…At the end, 53 samples had been obtained (9 traps x 6 times, although a sample got lost in the site 8 because the trap was removed, probably for a wild animal) and transferred to the laboratory where they were sorted and examined for Calliphoridae. Species of Calliphora, Lucilia and Chrysomya were identifi ed using the papers of Gonzalez-Mora & Peris (1988); Gonzalez-Mora (1989); Peris & Gonzalez-Mora (1991) while for the species of Pollenia we used the papers of Rognes (1987aRognes ( , 1987bRognes ( , 1991aRognes ( , 1991bRognes ( , 1992aRognes ( , 1992b. A list of the species can be found in the Table 1.…”
Section: Sampling Sites and Sampling Designmentioning
confidence: 99%
“…At the end, 53 samples had been obtained (9 traps x 6 times, although a sample got lost in the site 8 because the trap was removed, probably for a wild animal) and transferred to the laboratory where they were sorted and examined for Calliphoridae. Species of Calliphora, Lucilia and Chrysomya were identifi ed using the papers of Gonzalez-Mora & Peris (1988); Gonzalez-Mora (1989); Peris & Gonzalez-Mora (1991) while for the species of Pollenia we used the papers of Rognes (1987aRognes ( , 1987bRognes ( , 1991aRognes ( , 1991bRognes ( , 1992aRognes ( , 1992b. A list of the species can be found in the Table 1.…”
Section: Sampling Sites and Sampling Designmentioning
confidence: 99%
“…There are also small differences in feeding behaviour between the European strains of P. rudis and the North American strain (Yahnke & George 1972). These observations may not be the last word because Rognes (1987) noted that since "rudis" in North America in fact consists of three different species, it follows that nothing is known for certain about the life cycle of any cluster flies yet. Dear (1986) reported 32 endemic species of Pollenia from New Zealand, comprising 76% of the described world fauna in that genus (Kurahashi 1989).…”
Section: Introductionmentioning
confidence: 86%
“…Yahnke & George (1972) reported that larvae of P. rudis entered the earthworm through almost any point in the body wall, and that their posterior spiracles remained exposed during the whole feeding period, because the larvae did not move from the original point of penetration. However, Rognes (1987) found that larvae may leave the host and commence feeding either on healthier parts of the same worm or on a fresh worm. In addition, larvae penetrated the body of the worm, either singly or in groups of up to seven individuals, mostly from the dorsal side (Rognes 1987).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations